2015
DOI: 10.5664/jcsm.5080
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on the Efficacy of Continuous Positive Airway Pressure on the Manifestations of Ménière's Disease in Patients with Concomitant Obstructive Sleep Apnea Syndrome

Abstract: Objective:To evaluate the effect of continuous positive airway pressure (CPAP) therapy on Ménière's disease patients with concomitant obstructive sleep apnea syndrome (OSAS), since recent reports suggest OSAS may cause dysfunction of the vestibular system. Study Design: Prospective study using CPAP administered to patients diagnosed with "Defi nite Ménière's disease" according to the guidelines of the American Academy of OtolaryngologyHead and Neck Surgery and combined with OSAS. Pathologically, Ménière's dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 32 publications
(33 reference statements)
1
30
1
Order By: Relevance
“…As illustrated by the present case report, concomitant OSA is potentially such a comorbidity that has often been underappreciated. e prevalence of clinically significant OSAS in the general adult population has been reported to be at least 8.5% [7]. In a longitudinal study, the association between MD and OSA patients was studied based on a nationwide 9year longitudinal cohort database of 1,025,340 South Korean patients [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As illustrated by the present case report, concomitant OSA is potentially such a comorbidity that has often been underappreciated. e prevalence of clinically significant OSAS in the general adult population has been reported to be at least 8.5% [7]. In a longitudinal study, the association between MD and OSA patients was studied based on a nationwide 9year longitudinal cohort database of 1,025,340 South Korean patients [9].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MD has been reported to be between 12 and 46 per 100,000, with a geographical variation [ 7 ]. The otologist/neurotologist routinely manages MD patients, and standard medical therapy includes lifestyle changes such as dietary salt restriction and medications such as diuretics, migraine prophylaxis, and steroid therapy [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, robust evidences show OSA patients have higher prevalence of vertigo, tinnitus and sudden deafness than non-OSA people and repeated nocturnal hypoxemia may be the link between OSA and inner ear disease but warrants further research to confirm [4] , [5] , [6] , [7] , [8] . Preliminary reports showed that continuous positive airway pressure (CPAP) therapy improved both OSA and inner ear symptoms at the same time [6] , [9] . Consequently, vertigo, tinnitus and sudden deafness may be additional indications for the treatment of OSA.…”
Section: Updated Indications For Treating Osamentioning
confidence: 99%
“…The first line of treatment is to encourage the patient to change his lifestyle into a healthier one. Regulation of sleeping cycle, avoiding stress, caffeine, alcohol, and tobacco, and changing into a low salt diet should be advised [60][61][62]. Caffeine is accused to increase the endolymph volume due to its sympathomimetic actions, and it is suggested to be restricted to 100 mg/day by AAO-HNS [63].…”
Section: Lifestyle Changes and Low Salt Dietmentioning
confidence: 99%